Assessing Tenth-Grade Students’ Mathematical Literacy Skills in Solving PISA Problems - Hanan Shaher Almarashdi; Adeeb M. Jarrah (Social Sciences, 2023)
We tested the mathematical literacy (ML) proficiency of 204 grade 10 “advanced track” students in the United Arab Emirates (UAE) using 34 questions from the Programme for International Student Assessment (PISA) 2012 released items. Using a quantitative descriptive approach, we analyzed the performance of males (n = 106) and females (n = 98) on items spread across the four content subdomains (quantity, space and shape, change and relationship, and uncertainty), the processes of problem-solving (formulate, employ, reasoning, and interpret), and the four PISA contexts (personal, occupational, societal, and scientific) across six PISA proficiency levels. The test was formulated in three types of response format (multiple choice, closed- and open-ended). Results showed that overall student performance was in the very low category. Female students outperformed male students in all aspects of mathematical literacy. The highest percentage achieved in the modelling process was in the interpreting and then employ and formulate tasks. Students performed almost perfectly in problems that covered the uncertainty content area but fared poorly with problems dealing with change and relationship. Students performed better on personal mathematical problems than occupational, societal or scientific problems. These findings are important for UAE teachers regarding direct application to classroom practice and for researchers and officials to shape future research and recommendations for future new educational policies.